Pembelajaran Berdiferensiasi dalam Menulis Teks Deskripsi: Studi Kasus pada Siswa Kelas IX SMP Negeri 2 Bendo Magetan - Inez Ardelia Subiyanto; Sumarwati Sumarwati (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to describe the planning, implementation, and assessment of differentiated instruction in teaching descriptive text writing to ninth-grade students at SMP Negeri 2 Bendo, Magetan Regency. The study was conducted in response to students difficulties in generating ideas, selecting appropriate vocabulary, organizing ideas coherently, and producing vivid descriptive texts. This research employed a qualitative approach with a case study design. Data were collected through lesson plan observation, classroom observation, teacher interviews, and documentation of student learning products. The findings indicate that differentiated instruction was planned through a Merdeka Curriculum-based teaching module, diagnostic assessment, contextual material selection, and the use of PowerPoint, observation sheets, and tiered student worksheets. The implementation emphasized process and learning-environment differentiation through triggering questions, direct observation of real objects around the school, group work, individual scaffolding, immediate feedback, and reflection. Assessment was carried out continuously through diagnostic, formative, and summative assessment. Differentiated instruction helped students generate concrete ideas, organize their writing more systematically, increase motivation, and strengthen descriptive text writing skills. These findings affirm that differentiated instruction can serve as an adaptive strategy in Indonesian language learning at junior high school level.